Conformation and microenvironment of the active site of a low molecular weight 1,4-beta-D-glucan glucanohydrolase from an alkalothermophilic thermomonospora sp.: involvement of lysine and cysteine residues - Jagtap, Sharmili; Rao, Mala (Biochemical and Biophysical Research Communications, 2006)
Conformation and microenvironment at the active site of 1,4-beta-D-glucan glucanohydrolase was probed with fluorescent chemo-affinity labeling using o-phthalaldehyde. OPTA has been known to form a fluorescent isoindole derivative by cross-linking the proximal thiol and amino groups of cysteine and lysine. Modification of lysine of the enzyme by TNBS and of cysteine residue by PHMB abolished the ability of the enzyme to form an isoindole derivative with OPTA. Kinetic analysis of the TNBS and PHMB-modified enzyme suggested the presence of essential lysine and cysteine residues, respectively, at the active site of the enzyme. The substrate protection of the enzyme with carboxymethylcellulose (CMC) confirmed the involvement of lysine and cysteine residues in the active site of the enzyme. Multiple sequence alignment of peptides obtained by tryptic digestion of the enzyme showed cysteine is one of the conserved amino acids corroborating the chemical modification studies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: 1; 4-beta-D-glucan glucanohydrolase; active site microenvironment; Cysteine; lysine; OPTA; PHMB; Thermomonospora sp.; TNBS